2010
DOI: 10.1021/op100176u
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Insight into a Simple C−N Bond Formation via SN2 Displacement: A Synergistic Kinetics and Design of Experiment Approach

Abstract: A novel series of 1,2,4-triazol-3-yl-azabicyclo[3.1.0]hexanes was recently identified as new highly potent and selective dopamine (DA) D 3 receptor antagonists. This class of molecules deserved the Chemical Development special attention to quantify the reliability and robustness of the pivotal S N 2 displacement step between the 1,2,4-triazol-3-yl-halide derivative (4) and variously substituted azabicyclo[3.1.0]hexanes (5). To reach this goal we applied the classical Design of Experiment (DoE) approach, simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 14 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Using numerical techniques to guide the optimization procedure offers significant efficiency gains over iterative, experimental approaches alone. Optimization of experimental factors through response surface modeling is not uncommon; however, the unique ability to include time in the optimization via the DRSM model expands the optimization problem set to include time-dependent responses, such as productivity, cycle time, and stability.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Using numerical techniques to guide the optimization procedure offers significant efficiency gains over iterative, experimental approaches alone. Optimization of experimental factors through response surface modeling is not uncommon; however, the unique ability to include time in the optimization via the DRSM model expands the optimization problem set to include time-dependent responses, such as productivity, cycle time, and stability.…”
Section: Results and Discussionmentioning
confidence: 99%
“…A GSK development team 62 The results from the DoE study showed an adequate fit to the data and demonstrated that the high setting for all four factors, which corresponded to the previously existing reaction conditions, led to the highest yield within the design space. In other words, the DoE suggested no improved conditions.…”
Section: Organic Process Research and Developmentmentioning
confidence: 96%
“…A GSK development team developed a robust S N 2 displacement step in the synthesis of analogues of dopamine D 3 receptor antagonist SB-277011. The reaction between chloropropylthiotriazole 118 and amine-HCl salt 119 to provide 120 was plagued by the formation of impurity 121 arising from intramolecular cyclization of 118 (Scheme ).…”
Section: Review Of Selected Doe Manuscripts Published In Oprd From 20...mentioning
confidence: 99%
“…During our investigations, we observed that the nucleophilic displacement of the chloride atom by Meldrum’s acid ( 12 ) was slow, even when heating to reflux in MeCN. To promote this displacement, addition of a catalytic amount of potassium iodide accelerated the conversion rate, and full conversion into 10 was reached after 6 h at 50 °C. Nevertheless, the main drawback of using Meldrum’s acid ( 12 ) or malonate derivatives in this reaction was the formation of 10–20% a/a of overalkylated side product 13 .…”
Section: Homologation and Decarboxylationmentioning
confidence: 99%